616 MULTIMODAL TREATMENT OF LOCALLY ADVANCED ESOPHAGEAL SQUAMOUS CELL CARCINOMA: A NETWORK META-ANALYSIS. (17th September 2021) - Jin, Zixian; Chen, Dong; Chen, Meng; Ren, Sijia; Wang, Chunguo; Zhang, Bo; Zhang, Jian; Zhu, Hongyu; Xue, Fenglai; Wu, Sikai; Zhu, Chengchu; Shen, Jianfei
Abstract:  : The best treatment for the esophageal squamous cell carcinoma has not been determined. To determine the most effective and safest treatment mode for locally advanced resectable esophageal squamous cell carcinoma through a network meta-analysis. Methods: A Bayesian model was used for a network meta-analysis comparing the efficacy and safety of surgery alone, neoadjuvant therapy, and adjuvant therapy. Results: Overall survival rate: Adjuvant chemoradiotherapy and neoadjuvant chemoradiotherapy were significantly advantageous over surgery alone [hazard ratio (HR) 0.73, 95% confidence interval (CI) 0.57–0.93; HR 0.75, 95%CI 0.65–0.86]. Adjuvant chemotherapy may not be as effective as surgery alone [HR 1.08, 95%CI 0.84–1.39], although there was no statistical difference. There was no statistically significant difference between adjuvant chemoradiotherapy and neoadjuvant chemoradiotherapy. Disease-free survival rate: Compared with surgery alone, neoadjuvant chemoradiotherapy had significant benefits [HR 0.65, 95%CI 0.53–0.78]; adjuvant chemoradiotherapy had similar, but not significant, benefits [HR 0.7, 0.95%CI 0.45–1.06]. The difference between neoadjuvant chemoradiotherapy and adjuvant chemoradiotherapy was also not statistically significant. Conclusion: Both neoadjuvant chemoradiotherapy and adjuvant chemoradiotherapy appear to be the best supplements to surgery for locally advanced resectable esophageal squamous cell carcinoma.